Microfracture versus Enhanced Microfracture Techniques in Knee Cartilage Restoration: A Systematic Review and Meta-Analysis - Wen, Hong-Jie; Yuan, Li-Bo; Tan, Hong-Bo; Xu, Yong-Qing (The Journal of Knee Surgery, 2020)
This study aimed to compare the efficacy and safety of the microfracture (MFx) and microfracture augmented (MFx + ) techniques for the treatment of cartilage defects of the knee. The PubMed and EMBASE databases were searched from 1 January, 1950 to 1 May, 2019. RevMan5.3 was used to perform statistical analysis. Relative risk was calculated for binary variables, and weighted mean difference and standardized mean difference (SMD) were measured for continuous variables. The 95% confidence interval (CI) of each variable was assessed. Thirteen trials with 635 patients were included. There was a significant difference in the Lysholm's score (SMD = 0.26, 95% CI: 0.01–0.50, p = 0.04) and magnetic resonance observation of cartilage repair tissue score (SMD = 14.01, 95% CI: 8.01–20.02, p < 0.01) between the MFx and MFx+ groups. There was no significant difference in the Western Ontario and McMaster Universities Osteoarthritis Index score (SMD =  − 12.40, 95% CI: −27.50 to 32.71, p = 0.11), International Knee Documentation Committee score (SMD = 8.67, 95% CI: −0.92 to 18.27, p = 0.08), visual analog scale score (SMD =  − 0.20, 95% CI: −2.45 to 0.96, p = 0.57), Tegner's score (SMD = 0.26, 95% CI: −0.67 to 1.18, p = 0.59), modified Cincinnati's score (SMD =  − 4.58, 95% CI: −14.31 to 5.14, p = 0.36) and modified International Cartilage Repair Society pain score (SMD = 0.09, 95% CI: −0.37 to 0.55, p = 0.70) between the groups. Results of the pooled analyses of the MFx+ and MFx groups suggested that the MFx+ technique is slightly superior to the MFx technique for the treatment of articular cartilage defects of the knee. Further research is required and future studies should include assessments of the outcomes at long-term follow-ups. Trial registration number is PROSPERO CRD42019135803.
Keywords: microfracture; enhanced microfracture techniques; knee cartilage restoration; meta-analysis